PERBEDAAN SIKAP PRIMIGRAVIDA DAN MULTIGRAVIDA DALAM PERSIAPAN PERSALINAN DI BPM Hj. SOETARMI SW, SsiT., M.Kes SURAKARTA - ., Wijayanti; Dewi, Wiwik Puspita (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
Attitude represent or reaction of respons someone which still closed to a object or stimulus. In preparation before bearing among others, blocking in bearing, blocking in decision and benefactor of bearing, drawing up transportation system, drawing up blood donor if happened emergency serious, blocking in expense, and needed to equipments is bearing. In pregnant mother society phenomenon of primigravida tend to more worry with its its his because representing first experience and require many adaptation of physical, psychology, while calmer multigravida experiencing him because repeating its erstwhile experience. Target of this research to know difference of attitude of primigravida and of multigravida in preparation of bearing. This research use method of observational analytic by using approach of device of cross sectional. this Research Subject is pregnant mother of and primigravida of multigravida III trimester fulfilling criterion of inklusi and of eksklusi amounting to 30 primigravida and 30 multigravida in BPM Hj. Soetarmi Sw, SSiT, M.Kes Surakarta. Instrument the used is questioner. Analysis which is used in this research is statistical test of Chi Square. Result of this research indicate that mother of primigravida counted 15 people (50%) owning attitude with category ready to and counted 15 people (50%) owning attitude with category do not ready to, at all of mother of multigravida counted 30 people (100%) owning attitude with category ready to. Examination of Chi Square yield value Zhitung equal to 17,422. As for value Ztabel for examination with level of signifikansi 5% is equal to 3,841. Along of Zhitung > Ztabel (7,422 > 3,841), hence Ho refused and Ha accepted. Conclude from this research there is difference of attitude and primigravida of multigravida in preparation of bearing. Progressively often experience of bearing, hence attitude about preparation of bearing progressively ready to because repeating erstwhile him. Keyword : Difference, Attitude, Preparation of Bearing